1,3-Dicyclohexyl-3-[(pyridin-2-yl)carbonyl]urea monohydrate from synchrotron radiation - Pinheiro, Alessandra C. (International Union of Crystallography, 2011)
The title urea derivative crystallizes as a monohydrate, C(19)H(27)N(3)O(2)·H(2)O. The central C(3)N grouping is almost planar (r.m.s. deviation = 0.0092 Å), and the amide and pyridine groups are substantially twisted out this plane [dihedral angles = 62.80 (12) and 34.98 (10)°, respectively]. Supramolecular double chains propagating along the b-axis direction feature in the crystal packing whereby linear chains sustained by N—H⋯O hydrogen bonds formed between the amide groups are linked by helical chains of water molecules (linked by O—H⋯O hydrogen bonds). The H atom that participates in these water chains is disordered over two positions of equal occupancy. The double chains are connected into a two-dimensional array by C—H⋯O contacts and the layers stack along the a axis.